Koeksistensi Saeyyang Pattuqduq dalam Kehidupan Masyarakat Polewali Mandar: (Tinjauan Studi Historis dan Antropologi) - Wijdan, Wijdan Alim Lopa; Susmihara; Dewi Anggariani (Rihlah: Jurnal Sejarah dan Kebudayaan, 2024)
Traditional knowledge is a culture or intellectual property that is communal and passed down from generation to generation. One of the districts in West Sulawesi is Polewali Mandar Regency which has a cultural culture that contains a philosophy that has been passed down from their ancestors, namely Saeyyang Pattuqduq. The Saeyyang Pattuqduq tradition is a tradition of thanksgiving for children who have successfully memorized the Qur'an. This type of research is library research using several historical, anthropological and sociological approaches. The data collection methods used in this research are: observation, interview and documentation. The results of this study reveal that First, the form of cultural acculturation with Islamic religious teachings, namely Saeyyang Pattuqduq, stems from behavior. Second,. Third, it has value and attraction for all circles both within the domestic and foreign scope, the performance which is held annually is used as a form of Festival implementation.